Socio-economic status of fisherf(Jlk in relation to fish and fisheries of Hemavathy reservoir - Madhyastha, M N; Murugan, S (Indian Journal of Fisheries, 2011)
The Hemavathy reservoir has been constructedacross the River Hemavathy atGorur, Hassan district. The rivers Hemavathyand Yagachi which originate fromBallarayana Durga and Bababudangiri hillsof Western Ghat, respectively, form thesource of the reservoir. The reservoir has awaterspread area of about 2810 km2, and issituated at 12"04'0" Nand 76Â° 03'0" E at anelevation of 891 m MSL. The storage capacityis 37.10 TMC ft which can be used toirrigate approximately 0.28 million ha ofland. In addition to irrigation, the water isused for drinking and other domestic purposes.Extensive fishery activities practisedthis Reservoir have made a major source oflivelihood for the fishermen in its vicinity.Hence, the study was undertaken to understandand present suggestions to upgrade thestatus of the fishermen